2014
DOI: 10.1371/journal.pone.0085631
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and Selection Cause Codon Usage and Bias in Mitochondrial Genomes of Ribbon Worms (Nemertea)

Abstract: The phenomenon of codon usage bias is known to exist in many genomes and it is mainly determined by mutation and selection. To understand the patterns of codon usage in nemertean mitochondrial genomes, we use bioinformatic approaches to analyze the protein-coding sequences of eight nemertean species. Neutrality analysis did not find a significant correlation between GC12 and GC3. ENc-plot showed a few genes on or close to the expected curve, but the majority of points with low-ENc values are below it. ENc-plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 49 publications
3
53
0
Order By: Relevance
“…Had mutation pressure alone acted on these species, then we could have expected equal usage of AT and GC bases. Hence, our finding demonstrated that both natural selection and mutation might have influenced the codon pattern in mt‐protein coding genes of Bombina species, which supports the result of H. Chen, Sun, Norenburg, and Sundberg () in mtDNA of ribbon worm.…”
Section: Discussionsupporting
confidence: 86%
“…Had mutation pressure alone acted on these species, then we could have expected equal usage of AT and GC bases. Hence, our finding demonstrated that both natural selection and mutation might have influenced the codon pattern in mt‐protein coding genes of Bombina species, which supports the result of H. Chen, Sun, Norenburg, and Sundberg () in mtDNA of ribbon worm.…”
Section: Discussionsupporting
confidence: 86%
“…AT‐rich genome was also found in Plasmodium falciparum , Tetraphalerus bruchi , and Paranemertes cf. peregrine and Cephalothrix hongkongiensis …”
Section: Discussionmentioning
confidence: 99%
“…It is found to be endemic in some countries. Several surveys state that in Africa, urogenital schistosomiasis is due to the infection with S. haematobium (Chen et al 2014). In human it is caused by the penetration of infectious larvae (cercariae) through the skin of people.…”
Section: Introductionmentioning
confidence: 99%
“…Then in the body, adult schistosomes are developed from the larvae. For acute schistosomiasis (Katayama syndrome), the incubation period is found to be 14-84 days and characterized by headache, myalgia, diarrhea, fever and respiratory symptoms, but the chronic infection is thought to remain asymptomatic for many years (Chen et al 2014). For the standard diagnostics of urogenital schistosomiasis, a filtration technique is typically used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation